Design and Optimization of Cyproheptadine Hydrochloride Fastdissolving Tablet Using Design of Experiment - Bobde, Suwarna S. (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The aim of the current research project was to formulate and optimize a fast-dissolving tablet containing the antihistamine drug cyproheptadine hydrochloride (HCl), which is frequently used to treat allergies and other conditions. Materials and Methods: The direct compression method was used to prepare the fast-dissolving tablets of cyproheptadine HCl. Fourier-transform infrared spectroscopy was employed to evaluate the blend’s compatibility and ensure the stability of the active ingredient. The effect of two critical formulation variables: The amount of super-disintegrant (X1) and amount of effervescent agent (X2) – on the dependent variables: disintegration time (DT) (Y1), percentage drug release at 5 min (Y2), and percentage drug release at 10 min (Y3) – was examined using a two-factor, two-level Central Composite Design. Results: Design-Expert® software by Stat-Ease 360 trial version 13.0 was used to study the effect of formulation variables on dependent variables. Nine formulations were produced and assessed for several physicochemical characteristics as well as in vitro drug release. The data were analyzed using Response Surface Methodology and Analysis of variance. In comparison to other formulations, the software suggested an optimized formulation (CP OPT) with 5 mg of super-disintegrant and 49.572 mg of effervescent agent with shorter DT and a faster drug release, with over 85% of the drug being released in <10 min. Conclusion: The use of effervescence method with sodium starch glycolate, sodium bicarbonate, and other excipients resulted in fast dissolution of the drug in the tablet formulation. The effervescent technique enhanced in masking the bitter taste of the drug and it offered an effective approach for improving patient compliance and enhancing the therapeutic effects of cyproheptadine HCl through the development of fastdissolving tablets with desired properties.